Continuous Monitoring of Essential Tremor Using a Portable System Based on Smartwatch - Zheng, Xiaochen; Vieira Campos, Alba; Ordieres-Meré, Joaquín; Balseiro, Jose; Labrador Marcos, Sergio; Aladro, Yolanda (Frontiers in Neurology, 2017)
Introduction: Essential tremor (ET) shows amplitude fluctuations throughout the day, presenting challenges in both clinical and treatment monitoring. Tremor severity is currently evaluated by validated rating scales, which only provide a timely and subjective assessment during a clinical visit. Motor sensors have shown favorable performances in quantifying tremor objectively. Methods: a new highly portable system was used to monitor tremor continuously during daily lives. It consists of a smartwatch with a tri-axial accelerometer, a smartphone and a remote server. An experiment was conducted involving 8 ET patients. The average effective data collection time per patient was 26 (± 6.05) hours. Fahn-Tolosa Marin Tremor Rating Scale (FTMTRS) was adopted as the gold standard to classify tremor and to validate the performance of the system. Quantitative analysis of tremor severity on different time scales is validated. Results: Significant correlations was observed between neurologist’s FTMTRS and patient’s FTMTRS auto-assessment scores (r=0.84; p=0.009), between the device quantitative measures and the scores from the standardized assessments of neurologists (r=0.80; p=0.005) and patient’s auto-evaluation (r=0.97; p=0.032), and between patient’s FTMTRS auto-assessment scores day-to-day (r=0.87; p<0.001). A graphical representation of 4 patients with different degrees of tremor was presented and a representative system is proposed to summarize the tremor scoring at different time scales. Conclusion: This study demonstrates the feasibility of prolonged and continuous monitoring of tremor severity during daily activities by a highly portable nonrestrictive system, a useful tool to analyze efficacy and effectiveness of treatment.